WANGSALAN PADINAN, SASTRA LISAN WARISAN BUDAYA TAK BENDA: REFLEKSI DAN NILAI LUHUR MASYARAKAT JAWA - Widayati, Mukti; Nugrahani, Farida; Sudiyana, Benedictus; Diniseptiari, Wahyu (Prosiding Seminar Nasional dan Internasional HISKI, 2024)
This research aims to describe 1) the aesthetic structural patterns found in the wangsalan; 2) describe the meaning contained in the wangsalan; 3) describe the noble values contained in the wangsalan. Qualitative descriptive is the method of choice for expressing this meaning. The data required is in the form of speech that appears in wangsalan forms with data sources from texts in books, articles and sources (teachers, lecturers and Javanese culture activists). This data was collected by literature study and interviews. The data validity carried out was triangulation of sources and methods. The data was analyzed using content analysis techniques and applying semiotic structural theory. The end of this research resulted in several things. First, the wangsalan structure pattern that appears in daily Javanese conversations is the DM (Described Explained) pattern; second, the results of the semiotic analysis of the meaning of wangsalan are very closely related to communication between speakers and speakers indirectly to avoid conflict; third, the noble values of Javanese society which are reflected in the wangsalan are a reflection of Javanese society in everyday life, prioritizing balance and harmony in social life, being polite and humble in speaking, avoiding the use of words that are seen as harsh in order to hurt feelings, and prioritize harmony in life.